SIFAT ADSORPSI SELEKTIF KITOSAN TERCETAK IONIK TEMBAGA SELECTIVE ADSORPTION PROPERTIES OF COPPER IMPRINTED IONIC CHITOSAN - , DEWI WULANDARI; , Prof. Dr. Narsito ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The adsorption properties of copper ion imprinted chitosan have been studied through formation of chitosan-copper complex then followed by crosslinking with glutaraldehyde and release of metal ion precursor with Na2EDTA. Characterizations of KTI(Cu) were done by identification of functional group and gas sorption analyzer to determine its specific surface area. Adsorbent stabilities has been studied in acid medium with variations of pH. The adsorption of Cu(II) was conducted by using batch adsorption method as a function pH, and variety of Cu(II) ion concentrations. Adsorption selectivities of the adsorbents have studied in metal mixtures (Cu2+, Ca2+, and Zn2+). The analysis of Cu(II), Ca(II), and Zn(II) ions before and after adsorption were done by using atomic absorption spectrometry (AAS) method. The results showed that the characterization of the modification of chitosan into IIC(Cu) using FTIR gave information that the IIC(Cu) contained amine groups (NH2) and imine groups (C=N). Gas sorption analyzer confirmed that the IIC(Cu) has a smaller specific surface area, in the ranging from 1.38 m2/g to 1.56 m2 / g than cross-linked chitosan, CC which was in the range from 1.51 m2/g to 1.65 m2 / g. Adsorbent stabilities towards acid indicated that CC and IIC(Cu) were more stable (96.6 to 97%) than commercial chitosan (3%). Optimum condition for Cu(II) adsorption for each adsorbent occurred at pH 5. The adsorption capacities of Cu(II) ion based on Langmuir adsorption isoterm model showed that the largest adsorption capacity of Cu(II) with the amount of 44.22 mg/g was achieved by IIC(Cu) C (10000 mg/L Cu2+ and 1% glutaraldehyde) and CC (C) (1% glutaraldehyde) with the amount of 26.48 mg/g. The selective multimetal adsorption showed that IIC(Cu) has a high selectivity toward metal ion Cu(II) while CC has a low selectivity metal ion Cu(II) at different concentration of Cu(II)